Motor Skills and Visual Deficits in Developmental Coordination Disorder: A Narrative Review - Pinero‐Pinto, Elena; Romero-Galisteo, Rita Pilar; Sánchez González, María Carmen; Escobio-Prieto, Isabel (IOAP-MDPI, 2022)
Background: Developmental coordination disorder (DCD) is a developmental disorder in which numerous comorbidities seem to coexist, such as motor and visual impairment and some executive functions; Methods: A narrative review on motor and visual deficits in children with DCD was carried out; Results and Discussion: Fine and gross motor skills are affected in children with DCD. In addition, they seem to be related to visual deficits, such as difficulty in visual perception, sensory processing and visual memory. Limitations have also been found in accommodation. Interventions in children with DCD should be aimed at improving both aspects, since vision affects motor skills and vice versa; Conclusions: In children with DCD, who present a marked deficit in global shape processing, it causes an association between deficiencies in visual perception and motor skills.
Keywords: Visión -- Trastornos; Developmental coordination disorder; Visual deficits; Motor skills; Review; Motor skills deficits; Vision impairments; Motor performance